KESIAPAN GURU KELAS DALAM IMPLEMENTASI KURIKULUM MERDEKA DENGAN PENDEKATAN DEEP LEARNING DI SEKOLAH DASAR GUGUS KI HAJAR DEWANTARA KECAMATAN KRAMAT KABUPATEN TEGAL - Tien Kusumawati; Maufur; Dewi Apriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research investigates the readiness of primary school teachers within the Ki Hajar Dewantara Cluster, Kramat Sub-district, Tegal Regency, in implementing the Merdeka Curriculum integrated with the Deep Learning approach. The Merdeka Curriculum is designed to provide freedom and focus on developing students' potential, while the Deep Learning approach (in the educational context, not AI) emphasizes the profound understanding of concepts and the deep mastery of competencies with a narrower scope of material. Field phenomena indicate that although the Merdeka Curriculum has not been fully implemented smoothly, teachers are now faced with a new learning approach, namely Deep Learning, which is slated for adoption in 2025. Observations and interviews suggest existing challenges such as limited teacher understanding of both concepts, uneven distribution of technological infrastructure, and low parental involvement. This study aims to determine teachers' understanding, supporting factors, constraints faced, and the outcomes of implementing these two policies. The findings of this research are expected to serve as a reference for future researchers, assist school principals and teachers in navigating curriculum implementation, and provide input for schools in determining effective learning models.